Preparation and characterization of genipin-cross-linked silk fibroin/chitosan sustained-release microspheres - Zeng SG; Ye MW; Qiu JQ; Fang W; Rong MD; Guo ZH; Gao WF (Dove Medical Press, 2015)
Shuguang Zeng,1,* Manwen Ye,1,2,* Junqi Qiu,1 Wei Fang,1 Mingdeng Rong,1 Zehong Guo,1 Wenfen Gao11Department of Oral and Maxillofacial Surgery, Guangdong Provincial Stomatological Hospital, Southern Medical University, 2Department of Stomatology, Guangdong Women and Children Hospital, Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workAbstract: We report the effects of distinct concentrations of genipin and silk fibroin (SF):chitosan (CS) ratios on the formation of SF–CS composite microspheres. We selected microspheres featuring an SF:CS ratio of 1:1, encapsulated various concentrations of bovine serum albumin (BSA), and then compared their encapsulation efficiency and sustained-release rate with those of pure CS microspheres. We determined that the following five groups of microspheres were highly spherical and featured particle sizes ranging from 70 µm to 147 µm: mass ratio of CS:SF =1:0.5, 0.1 g or 0.5 g genipin; CS:SF =1:1, 0.05 g or 1 g genipin; and CS:SF =1:2, 0.5 g genipin. The microspheres prepared using 1:1 CS:SF ratio and 0.05 g genipin in the presence of 10 mg, 20 mg, and 50 mg of BSA exhibited encapsulation efficiencies of 50.16%±4.32%, 56.58%±3.58%, and 42.19%±7.47%, respectively. Fourier-transform infrared spectroscopy (FTIR) results showed that SF and CS were cross-linked and that the α-helices and random coils of SF were converted into β-sheets. BSA did not chemically react with CS or SF. Moreover, thermal gravimetric analysis (TGA) results showed that the melting point of BSA did not change, which confirmed the FTIR results, and X-ray diffraction results showed that BSA was entrapped in microspheres in a noncrystalline form, which further verified the TGA and FTIR data. The sustained-release microspheres prepared in the presence of 10 mg, 20 mg, and 50 mg of BSA burst release 30.79%±3.43%, 34.41%±4.46%, and 41.75%±0.96% of the entrapped BSA on the 1st day and cumulatively released 75.20%±2.52%, 79.16%±4.31%, and 89.04%±4.68% in 21 days, respectively. The pure CS microspheres prepared in the presence of 10 mg of BSA burst release 39.53%±1.76% of BSA on the 1st day and cumulatively released 83.57%±2.33% of the total encapsulated BSA in 21 days. The SF–CS composite microspheres exhibited higher sustained release than did the pure CS microspheres, and thus these composite microspheres might function as a superior drug carrier.Keywords: silk fibroin, chitosan, genipin, microspheres, controlled release